"Doing diversity": a narrative examination of veteran teachers' renewed agency through intersectional teaching. Issue 1 (31st December 2020) - Shelton, Stephanie Anne; Melchior, Shelly
Abstract : Purpose: This paper aims to examine how two White teachers, experienced and award-winning veteran educators, navigated issues of race, class and privilege in their instruction, and ways that their efforts and shortcomings shaped both teacher agency and classroom spaces. Design/methodology/approach: This study's methodology centers participants' experiences and understandings over the course of two years of interviews, classroom observations and discussion groups. The study is conceptually informed by Sara Ahmed's argument that social justice is often approached as something that education "can do, " which is problematic because it assumes that successful enactment is "intrinsic to the term." Discussing and/or intending social justice replaces real change, and those leading the conversations believe that they have made meaningful differences. Instead, true shifts in thinking and action are "dependent on forms of institutional commitment […and] how it [diversity/social justice] gets taken up" (p. 241). Findings: Using an in vivo coding approach – i.e. using direct quotations of participants' words to name the new codes – the authors organized their findings into two discussions: "Damn – Every Time I'm with the Kids, I Just End Up Feeling Frozen"; and "Maybe I'm Just Not Giving These Kids a Fair Shake – Maybe I'm the Problem". Originality/value: The participants centered a participatory examination of intersectionality, rather than the previous teacher-mandated one. They "put into action" -xplorations of intersectionality that were predicated on students' identities and experiences, thus making intersectionality a lived concept, rather than an intellectual one, and transforming students' and their own engagement.